2014
DOI: 10.1016/j.ijinfomgt.2014.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Privacy in social networks: An analysis of Facebook

Abstract: Öz

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 6 publications
0
10
0
4
Order By: Relevance
“…Several studies have demonstrated the influence of prolonged use of Facebook on the psychological characteristics (attitudes and behaviors) of users (Amichai-Hamburger & Vinitzky, 2010;Correa et al, 2010;Dickie & Meier, 2015;Hayes et al, 2015;Lönnqvist & große Deters, 2016;Ross et al, 2009;Ryan & Xenos, 2011;Sagioglou & Greitemeyer, 2014;Shen et al, 2015;Wilson, Fornasier, & White, 2010). Some other existing studies pinpoint the effect of Facebook media interaction between users (Brailovskaia & Bierhoff, 2016;Mendes, Furtado, Militao, & de Castro, 2015), and several other studies have been carried out to investigate the privacy, trust and security concerns on Facebook (Junior, Xavier, & Prates, 2014;Külcü & Henkoğlu, 2014;Saeri, Ogilvie, La Macchia, Smith, & Louis, 2014;Tsay-Vogel et al, 2016).…”
Section: Facebook Literature Reviewmentioning
confidence: 99%
“…Several studies have demonstrated the influence of prolonged use of Facebook on the psychological characteristics (attitudes and behaviors) of users (Amichai-Hamburger & Vinitzky, 2010;Correa et al, 2010;Dickie & Meier, 2015;Hayes et al, 2015;Lönnqvist & große Deters, 2016;Ross et al, 2009;Ryan & Xenos, 2011;Sagioglou & Greitemeyer, 2014;Shen et al, 2015;Wilson, Fornasier, & White, 2010). Some other existing studies pinpoint the effect of Facebook media interaction between users (Brailovskaia & Bierhoff, 2016;Mendes, Furtado, Militao, & de Castro, 2015), and several other studies have been carried out to investigate the privacy, trust and security concerns on Facebook (Junior, Xavier, & Prates, 2014;Külcü & Henkoğlu, 2014;Saeri, Ogilvie, La Macchia, Smith, & Louis, 2014;Tsay-Vogel et al, 2016).…”
Section: Facebook Literature Reviewmentioning
confidence: 99%
“…The privacy calculus model argues that individuals perform a costs-benefits analysis before self-disclosure (Dinev & Hart, 2006). In the context of mobile social interactions, one of the major threats of self-disclosure is the concerns for privacy invasion (Külcü & Henkoğlu, 2014). Users who disclose personal information may obtain social rewards, such as developing and maintaining intimate relationships with peers or monetary rewards, such as coupons, cash bonuses, and discounts.…”
Section: Self-disclosure and Privacy Calculusmentioning
confidence: 99%
“…The privacy calculus model, which argues that self-disclosure intentions are determined by the rational calculus of the benefits and costs of privacy behaviours, is widely adopted in information system (IS) literatures (Dinev & Hart, 2006;Jiang, Heng, & Choi, 2013;Wang, Duong, & Chen, 2016). Külcü and Henkoğlu (2014) revealed that the concern for the loss of privacy is a significant barrier for self-disclosure in the information age. Monetary rewards, such as cash bonus, discounts and coupons can compensate the privacy concerns of disclosing personal information in online transactions (Posey, Lowry, Roberts, & Ellis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In social media usage, it is observed that women pay more attention to privacy than male users. (De Wolf, Willaert & Pierson, 2014;Hoy & Milne, 2010;Külcü & Henkoğlu, 2014, Litt, 2013.Therefore today's scientific studies focus on the privacy of the Internet, and in a significant majority of the studies, privacy is addressed in the axis of concern for the violation of the privacy of the individual (Yıldırım, 2016). Taddicken (2013) in his research, studied privacy concerns on the Internet self-disclosure behavior.…”
Section: Introductionmentioning
confidence: 99%